PEMBUATAN PETA JALUR EVAKUASI BERBASIS SISTEM INFORMASI GEOGRAFIS UNTUK SOSIALISASI KESIAPSIAGAAN STAKEHOLDER DALAM MENGHADAPI BENCANA BANJIR - Cahyono, Hendro (Jurnal Geografi, 2016)
The goal of this research was Creation of Flood Disaster Evacuation Map to improve community preparedness infacing floods. Floods in Pati regency in 2014 was the most severe disaster in the last 20 years. Worst flood disastersoccurred in central part of Pati regency which caused by Juwana river. One of disaster management effort was doingtrial or socialization of Flood Evacuation Path Map to stakeholders in central part of Pati regency. The stakeholderswere BPBD, SAR, chief of Village and Karang Taruna. This was experiment research. Data collection methods useddocumentation, observations, questionnaires and tests. Data were analyzed using descriptive quantitative and gain test.Results of the study includes disaster data, Flood Evacuation Path Map and contribution of map as media in communitypreparedness toward floods. Based on disaster data compilation obtained zoning of flood height, the affectedsettlements, flood evacuation route, and the logistic support path. Creation of preparedness media Flood EvacuationPath Map which is feasible in terms of content and design. Socialization has increased the average value of the resultsafter using the media of Flood Evacuation Path Map with relative socialization outcome was in high category. It can beconcluded that the Flood Evacuation Path Map contributed to increase preparedness of Central part of Pati regencycommunity toward floods.